An in-depth Analysis of the New Dimensions of China-Pakistan Cooperation from the Perspective of the Community of Human Destiny: Strategy, Challenges and Prospects - zhou, xinmei; ma, xinyu; gong, hongwen (Pacific International Journal, 2024)
Abstract: Currently, the regional and global environment is evolving rapidly, and the geopolitical landscape in South Asia presents even more complexity and challenges.Against this backdrop, enhancing China-Pakistan collaboration and expediting the establishment of a China-Pakistan community of common destiny will contribute to upholding regional stability. Both China and Pakistan are dedicated to fostering peace and progress, collaborating in fields such as culture, science and technology, education, while championing equity and justice on a global scale. China’s idea of a shared human destiny finds manifestation in the relations between China and Pakistan. The two nations have bolstered strategic partnership founded on mutual respect, striving together for peace and prosperity in both the region and the world.